A Comparison Between SRSS-IE and BASC-2 BESS Scores at the Middle School Level. (May 2019) - Lane, Kathleen Lynne; Oakes, Wendy Peia; Common, Eric Alan; Brunsting, Nelson; Zorigian, Kris; Hicks, Tyler; Lane, Nathan A.
We report findings of a psychometric study comparing scores from two screening tools: Student Risk Screening Scale–Internalizing and Externalizing (SRSS-IE, an adapted version of the Student Risk Screening Scale) and Behavior Assessment System for Children–Second Edition, Behavioral and Emotional Screening System (BASC-2 BESS). Participants were 624 sixth-, seventh-, and eighth-grade students attending a rural middle school in a southeastern state. Pearson correlation coefficients indicated statistically significant, positive relations between SRSS-IE and BASC-2 BESS scores, with very strong relations on externalizing and comorbid (internalizing and externalizing) scales. Results of concurrent classification accuracy analyses, kappa, and receiver operating curve analyses suggest the seven externalizing items on the SRSS (SRSS-E7) and BASC-2 BESS scores function in a similar manner with respect to detecting students with externalizing behaviors, but less so in detecting students with internalizing behaviors. Limitations and future direction are discussed.